Enrichment of Water FleasUsingSpirulinaplatensisFlourWithDifferentDoses of GrowthandSurvivalRate of GoldfishLarvae (Carasiusauratus) - Sintia Rahma; Netti Aryani; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstrakThisresearchwasconductedfrom November toDecember 2017 atFishBreedingLaboratory, Faculty of FisheriesandMarine, University of Riau.The aim of thisresearchistoknowtheeffect of enrichmentwaterfleasusingSpirulinaplatensisflourwithdifferentdoses of growthandsurvivalrate of goldfishlarvae (Carasiusauratus). The methodusedinthisstudyisanexperimentalmethodwithCompletelyRandomizedDesign (RAL) withthreetreatmentsandthreerepetitions, such as thetreatments PS3 (waterfleaswithdoses 3 g/l), PS5 (waterfleaswith dioses 5 g/l), PS7 (waterfleaswith dioses 7 g/l). Parametersmeasuredisabsoluteweightgrowth, absolutelonggrowth, dailyweightgrowthrateandsurvival. The resultsshowedthatenrichmentwaterfleasusingSpirulinaplatensiswithdoses 7 g/l gaveeffectthebestwas on absoluteweightgrowthwas 0,64 grams, absolutelonggrowthwas 2,94 cm, dailyweightgrowthratewas 11,2 % / dayandthesurvivalratewas 84,44%.Keywords : Spirulinaplatensis, goldfishlarvae